Detrimental proarrhythmogenic interaction of Ca2+/calmodulin-dependent protein kinase II and NaV1.8 in heart failure - Philipp Bengel (Nature Portfolio, 2021)
In heart failure, increased CaMKII activity is decisively involved in arrhythmia formation. Here, the authors introduce the neuronal sodium channel NaV1.8 as a CaMKII downstream target as its specific knock-out reduces arrhythmias and improves survival in a CaMKII-overexpressing mouse model.